Systematic assessment of triticale‐based biorefinery strategies: environmental evaluation using life cycle assessment1. (31st August 2018) - Liard, Gladys; Lesage, Pascal; Samson, Réjean; Stuart, Paul R
Abstract: Triticale ( X Triticosecale Wittmack) is a non‐food energy crop with potential as a biorefinery feedstock. In addition to technical, economical, and commercial risks, it is of critical importance that environmental issues be considered in the decision‐making process regarding the development of the triticale‐based biorefinery. In this study, life cycle assessment (LCA) has been used for this purpose. To facilitate overall decision‐making including economic and other metrics, the number of environmental indicators should be minimized, and yet at the same time, these indicators should be representative, comprehensive, and easy to interpret. To identify such a set of environmental indicators from LCA results, a multi‐criteria decision‐making (MCDM) panel study was carried out and an external set of normalization factors used to assist in this decision‐making context. The influence of eight technology choices on the environmental impacts resulting from the production of ethanol, polylactic acid (PLA), and thermoplastic starch (TPS) blend was assessed. Moreover, the environmental benefits of improved triticale yield and its ability to grow on marginal land were assessed. Although the complete spectrum of environmental impact categories was evaluated, the MCDM panel selected four criteria to be brought forward to an overall decision‐making panel. The greenhouse gas (GHG) emissions metric was judged as the most important, followed by non‐renewable resource depletion, cropland occupation, and human health. Moreover, it was shown that certain technology choices such as ultra‐filtration and cogeneration significantly influence the environmental impacts of the triticale biorefinery. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd